Menulis Kritis Teks Eksposisi dengan Assessment as Learning Bahan Ajar Kelas VIII - Yulis Mariasih; Titik Harsiati; Endah Tri Priyatni (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: Critical writing needs to be taught to junior high school students to develop analytical skills, evaluate, and relate meaningful learning experiences. Assessment as Learning (AaL) is an assessment that students can do to reflect on the development of their knowledge independently. Aal can be used as a variation of assessment in teaching materials. Critical writing and AaL can be combined in the form of teaching materials. This study will explain how AAL and critical writing are part of the development of exposition text teaching materials for class VIII. This presentation was developed with a research development scheme by adapting the 4D development research model. Furthermore, from the research, the final result was that the application of AAL in the development of teaching materials could have a positive effect on students with a practice test score of 90% and product user trials with a score of 87%.Abstrak: Menulis kritis perlu diajarkan pada siswa SMP untuk mengembangkan kemampuan analisis, mengevaluasi, dan menghubungkan pengalaman belajar yang bermakna.   Assessment as Learning(AaL) merupakan penilaian yang dapat dilakukan siswa untuk merefleksi perkembangan pengetahuannya  secara mandiri. Aal dapat dijadikan sebagai variasi penilaian dalam bahan ajar. Menulis kritis dan AaL dapat dipadukan dalam bentuk bahan ajar. Penelitian ini akan menjelaskan bagaimana Aal dan menulis kritis menjadi bagian dari pengembangan bahan ajar teks eksposisi untuk kelas VIII. Paparan ini dikembangkan dengan skema penelitian pengembangan dengan mengadaptasi model peneltian pengembangan 4D. Selanjutnya dari penelitian terebut diperoleh hasil akhir bahwa penerapan Aal dalam pengembangan bahan ajar dapat memberikan pengaruh yang positif bagi peserta didik dengan skor ujicba praktisi dan ahli sbesar 90% serta uji coba pemakai produk dengan skor 87%.